Pengembangan software pemesanan tiket bioskop berbasis Odoo ERP dengan Metode Scrum - HAT, Aqza Tri Ananda; Susanto, Moh. Heri; Fata, Muhammad Emillul; Supriyono, Supriyono (Maliki Interdisciplinary Journal, 2024)
The development of internet technology has changed how consumers make purchases online, encouraging software to keep up with these changes. Thus, this study aims to develop a cinema ticket booking software based on Odoo ERP using the Scrum method. Odoo ERP was chosen as the development platform because it has the ability to manage various business processes needed in ordering cinema tickets online. The Scrum method was chosen because of its ability to overcome challenges in software development focusing on customer needs and fast market demands. The Scrum cycle development process includes sprint planning, daily scrum, sprint review, and sprint retrospective which uses agile principles, is done incrementally and iteratively, and is flexible. In this study, it shows that the development of cinema ticket ordering software using the scrum method has been successful. In which, the film list input and ticket input features were added to find out which films are available and select the film you want to watch. Overall this software makes it easy for users to process ticket orders. So that this research can be a guide for companies in choosing the appropriate technology and development strategy to improve ticket booking services in the entertainment industry.